2023
DOI: 10.1242/jcs.260327
|View full text |Cite
|
Sign up to set email alerts
|

CCDC66 regulates primary cilium length and signaling via interactions with transition zone and axonemal proteins

Abstract: The primary cilium is a microtubule-based organelle that serves as a hub for many signaling pathways. It functions as part of the centrosome/cilium complex, which also contains the basal body and the centriolar satellites. Little is known about the mechanisms by which the microtubule-based ciliary axoneme is assembled with proper length and structure, particularly in terms of the activity of microtubule-associated proteins (MAPs) and the crosstalk between the different compartments of the centrosome/cilium com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…Based on our own and previously published co-immunoprecipitation experiments, the interactions of CCDC66 and CSPP1 with CEP104 depended on its jelly-roll (JR) domain (Fig. S2C) (Frikstad et al, 2019; Odabasi et al, 2023). The deletion of this domain abolished the ability of both proteins to recruit CEP104 to MTs (Fig.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…Based on our own and previously published co-immunoprecipitation experiments, the interactions of CCDC66 and CSPP1 with CEP104 depended on its jelly-roll (JR) domain (Fig. S2C) (Frikstad et al, 2019; Odabasi et al, 2023). The deletion of this domain abolished the ability of both proteins to recruit CEP104 to MTs (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Since recent studies described functional and biochemical interactions between CEP104, CCDC66, CSPP1 and ARMC9 (Frikstad et al, 2019; Latour et al, 2020; Odabasi et al, 2023), we next tested in vitro the combinations of these proteins. We found that in the presence of 15 nM CCDC66, already 2 nM CEP104 was sufficient to occasionally block MT plus end outgrowth from the seed (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 7 ] Dysregulation of cilium length causes multiple types of organ dysfunction, leading to a class of diseases called ciliopathies. [ 8 ] Therefore, understanding how cilium length is regulated will provide new perspectives for the treatment and prevention of ciliopathies.…”
Section: Introductionmentioning
confidence: 99%